Cancer Burden Disease Attributable to PM2.5 and Health Risk by PM2.5-bound Toxic Species in Two Urban Chilean Municipalities - Ye Li; Franz Muñoz-lbañéz; Ana Maldonado-Alcaíno; Darby Jack; Beizhan Yan; Li Xu; Marco Acuña; Manuel Leiva-Guzman; Ana Valdés; Dante D. Cáceres (Aerosol and Air Quality Research)
Abstract This study aimed to estimate the environmental cancer disease burden in adults attributable to fine particulate matter (PM2.5) exposure using Ostro’s function methodology, and health risk indexes for particle-bound toxic chemicals through hazard quotients (HQ, HI) and carcinogenic risk (CR, CRI) indexes from EPA guidelines, of two urban Chilean Municipalities: Coyhaique and Independencia. Quantification of chemical species (OC, EC, metals, and PAHs) was done at the Lamont-Doherty Earth Observatory of Columbia University, USA. Modern carbon in OC and EC analysis showed that the principal source of PM2.5 emission in Coyhaique was firewood burning compared with Independencia. The total PAHs and B[a]P concentrations were 6.3 and 8.9 times higher in Coyhaique than in Independencia. In contrast, As and Pb levels were significantly greater in Independencia. The HI was 14.5 and 2.37 times the limit considered acceptable (HI > 1) in Coyhaique and Independencia, explained 92.45% by B[a]P and 66.99% by As, respectively. CRI exceeded the threshold (1 × 10−6) in Coyhaique and Independencia, explained by As (75.38%) plus B[a]P (20.30%) and As (97.01%). The attributable fraction (AF) of deaths due to lung cancer from long-term exposure to PM2.5 reached 54% (95% CI: 25–72) in Coyhaique vs. 43% (95% CI: 19–46) in Independencia. The AF for cardiopulmonary cancer were 40% (95% CI: 17–57) and 32% (95% CI: 12–46), respectively. A relevant fraction of the cancer cases and potential expected adverse effects would be attributable to long-term exposure to PM2.5 and the presence of chemical compounds bound to the particles. These results deserve further study to help guide policy in different environments, mainly carcinogenic PM2.5-bound toxic species from other emission sources, particularly firewood burning.